2008
DOI: 10.1016/j.jmb.2008.06.090
|View full text |Cite
|
Sign up to set email alerts
|

d-Ribose-5-Phosphate Isomerase B from Escherichia coli is Also a Functional d-Allose-6-Phosphate Isomerase, While the Mycobacterium tuberculosis Enzyme is Not

Abstract: SummaryInterconversion of D-ribose 5-phosphate and D-ribulose 5-phosphate is an important step in the pentose phosphate pathway. Two unrelated enzymes with D-ribose-5-phosphate isomerase activity were first identified in Escherichia coli, RpiA and RpiB. In this organism, the essential 5-carbon sugars were thought to be processed by RpiA, while the primary role of RpiB was suggested instead to be interconversion of the rare 6-carbon sugars, D-allose 6-phosphate and D-allulose 6-phosphate. In Mycobacterium tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…The active site of LacAB is coterminous with that of RpiB, except that Arg-39 (LacB) of LacAB replaces Asp-42 of Mt RpiB and interacts with the phosphate group of hexose phosphate, instead of Arg-113 in Mt RpiB [30,31]. LacAB and RpiB also differ with respect to the shape and size of the substrate-binding pocket.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The active site of LacAB is coterminous with that of RpiB, except that Arg-39 (LacB) of LacAB replaces Asp-42 of Mt RpiB and interacts with the phosphate group of hexose phosphate, instead of Arg-113 in Mt RpiB [30,31]. LacAB and RpiB also differ with respect to the shape and size of the substrate-binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…The primary factor that determines the pocket size is the location of Arg-130 (LacA), Arg-134 (LacA), and Arg-39 (LacB) to form the outside frame of the pocket. These three long and flexible arginine side chains interact with the phosphate moiety of the substrate and can change its direction away from the catalytic residue in order to accommodate the six-carbon substrate [31]. Superimposition of the LacAB and Mt RpiB structures showed that Gly-129 (LacA) and Arg-130 (LacA) of the α6 helix are shifted toward the C-terminal α7 helix of LacB, with the movement of Cα atoms by 2.43 Å and 2.22 Å, respectively, for an overall Cα root-mean-square deviation of 1.2 Å.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. pu is Streptococcus pneumonia (2PPW, no primary citation), V. pa is Vibrio parahaemolyticus (3ONO, no primary citation), T. ma is Thermotoga maritima (PDB ID 1O1X) [19], E. co is E. coli (1NN4) [2], C. th is Clostridium thermocellum (3HEE) [14], T. cr is Trypanosoma cruzi (3K8C) [6]. Mycobacterium tuberculosis contains different active site residues and utilizes a variant catalytic mechanism [5,22], and thus the sequence is not shown in the alignment. Residues marked with an * are involved in recognition of the phosphate moiety of ribose-5-phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…Given the important cellular role of ribose-5-phosphate isomerases and that mammals only have RpiA, interest has been generated in RpiB enzymes as potential drug targets, especially in pathogenic organisms, many of which only have RpiB. E. coli RpiB inhibitors have been described [4] and inhibitor-bound crystal structures have been determined for RpiB from Mycobacterium tuberculosis [5] which causes tuberculosis and Trypanosma cruzi [6], the causative agent of trypanosomiasis.…”
Section: Introductionmentioning
confidence: 99%